RELASI BAHASA DAN OTAK SERTA GANGGUAN BERBAHASA DALAM PEMBELAJARAN BAHASA ARAB - Yulyana Dewi Nabilah; Nevin Nismah; Shofil Fikri (Tarling : Journal of Language Education, 2024)
ABSTRACT Communication among humans is facilitated through language, which encompasses both spoken and written expressions organized in a structured manner. Language processing involves different parts of the brain, including areas involved in sound processing, word recognition and linguistic memory. This is important because knowledge of how the brain interacts with language can help in designing more effective teaching methods. Alongside the potential for success, students learning Arabic may also acquire language disorders. The objective of this research is to offer a comprehensive understanding of the relationship between language and the brain in the realm of Arabic language learning, as well as its disorders. The research employs a qualitative approach coupled with a literature study method. Data is gathered from diverse literature sources, including books, journals, and scientific articles that precede the current research. The chosen method for data analysis in this research is the content analysis method. The outcome of this research reveals the existence of language and brain relationships and interference in Arabic language learning through research and tests that have been conducted by previous researchers.